2016
DOI: 10.1016/j.tranon.2016.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Induction Chemotherapy Plus Intensity-Modulated Radiotherapy (IMRT) Versus IMRT Plus Concurrent Chemotherapy for Locoregionally Advanced Nasopharyngeal Carcinoma: A Propensity Matched Study

Abstract: PURPOSE: It deserves investigation whether induction chemotherapy (IC) followed by intensity-modulated radiotherapy (IMRT) is inferior to the current standard of IMRT plus concurrent chemotherapy (CC) in locoregionally advanced nasopharyngeal carcinoma. METHODS: Patients who received IC (94 patients) or CC (302 patients) plus IMRT at our center between March 2003 and November 2012 were retrospectively analyzed. Propensity-score matching method was used to match patients in both arms at equal ratio. Failure-fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…It is important to note that the 2-dimension RT technology was used for NPC patients in all the studies mentioned above. QuYang et al conducted a retrospective study to investigate the efficacy of 94 NPC patients receiving additional NAC to IMRT alone in 302 NPC patients treated with CCRT, and found comparable long-term survival outcomes 32 . A recent retrospective study conducted by Yao et al exhibited that the treatment outcomes in the NAC + RT group were similar to those in the CCRT group, with less acute and later toxicities for 214 patients with ascending-type NPC 33 .…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that the 2-dimension RT technology was used for NPC patients in all the studies mentioned above. QuYang et al conducted a retrospective study to investigate the efficacy of 94 NPC patients receiving additional NAC to IMRT alone in 302 NPC patients treated with CCRT, and found comparable long-term survival outcomes 32 . A recent retrospective study conducted by Yao et al exhibited that the treatment outcomes in the NAC + RT group were similar to those in the CCRT group, with less acute and later toxicities for 214 patients with ascending-type NPC 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Though equal therapeutic effects were observed, NACT plus IMRT decreased 10%‐15% of grade 3/4 adverse reactions, including MS, OM, XS and hearing loss . A study by OuYang et al achieved analogous results in NPC patients with stage II‐IVB disease . Lin et al and Liu et al further analyzed patients diagnosed with stage II‐IVB NPC and treated with NACT.…”
Section: Discussionmentioning
confidence: 97%
“…Although there was no prospective randomized trial published investigating the therapeutic value of IC followed by IMRT, retrospective studies and meta-analyses had shown high efficacy with low toxicities [20][21][22][23][24] in patients with LA-NPC. Lin et al suggested that IC plus IMRT resulted in superb 3-year PFS, OS, LRRFS, and DMFS.…”
Section: Discussionmentioning
confidence: 99%
“…Another propensity-matched study retrospectively analyzing 396 patients to investigate the efficacy of IC plus IMRT and CCRT in LA-NPC also observed no significant survival differences. 23 of grades 3 or 4 nausea-vomiting and leukopenia. 24 A metaanalysis analyzing 8 studies and 2605 patients showed IC plus RT achieved similar PFS, OS, LRRFS, and DMFS as IC plus CCRT and resulted in less hematological toxicities during radiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation